Pandora the curious - Holub, Joan (Holub, Joan. Goddess girls, 2012)
Pandora is famous among her classmates at Mount Olympus Academy for being curious, but when one of the godboys brings a mysterious box to school, her curiosity about what is inside it will create more trouble than she could have imagined.